Out of Empire Redefining Africa's Place in the World (Volume 8) - Cooper, Frederick (2013)
The history of decolonization is usually written backward, as if the end-point (a world of juridically equivalent nation-states) was known from the start. But the routes out of colonial empire appear more varied. Some Africans sought equal rights within empire, others to federate among themselves; some sought independence. In London or Paris, officials realized they had to reform colonial empires, but not necessarily give them up. The idea of "development" became a way to assert that empires could be made both more productive and more legitimate. Frederick Cooper explores how these alternative possibilities narrowed between 1945 and approximately 1960.